Incomplete recovery in patients with minor head injury directly discharged home from the emergency department: a prospective cohort follow-up study - Bram Jacobs; Joukje van der Naalt; Jan Cornelis ter Maaten; Sophie Maria Coffeng; Laura Jane Kim (BMJ Open)
Objectives To determine the frequency of post-traumatic complaints and recovery rate of non-hospitalised patients with minor head injury (MHI) and their relationship with demographic and injury characteristics. We also evaluated the differences between patient groups in this least severe category of brain and head injury.Design Prospective cohort follow-up study.Setting Patients admitted to the emergency department (ED) of a tertiary hospital in the Netherlands.Participants 242 patients with MHI (n=100 with head injury only and n=142 with mild traumatic brain injury (mTBI)) discharged home directly after evaluation at the ED.Outcome measures The primary outcome measure was incomplete recovery at 3 months measured by the Glasgow Outcome Scale-Extended score <8. Secondary outcome measures were number of post-traumatic complaints assessed 2 weeks and 3 months postinjury by a standardised questionnaire. Also the number of patients that visited their general practitioner because of persistent complaints was determined.Results Three months postinjury 48% of patients reported more than one post-traumatic complaint. Half (51%) of patients showed incomplete recovery. Incomplete recovery was associated with headache directly postinjury (OR 3.27, 95% CI 1.28 to 8.34), age (OR 1.02, 95% CI 1.00 to 1.05) and the number of post-traumatic complaints (OR 1.24, 95% CI 1.09 to 1.40) and depression (OR 6.31, 95% CI 1.24 to 32.00) 2 weeks postinjury. Incomplete recovery was comparable between the head injury only and mTBI group (55% vs 50%, 95% CI −12.5 to −23.0). In total 36 MHI patients (28%) visited their general practitioner because of complaints related to their head injury.Conclusion Half of the non-hospitalised patients with MHI experienced incomplete recovery after 3 months without differences between head injury only and mTBI patients. Therefore, early identification of patients at risk for incomplete recovery must be started at the ED to provide appropriate aftercare to avoid long-term post-traumatic complaints.